The Effect of Medicare's Prospective Payment System on Discharge Outcomes of Skilled Nursing Facility Residents - Walter P. Wodchis; Brant E. Fries; Richard A. Hirth (SAGE Publishing, 2004)
In July 1998, the Centers for Medicare and Medicaid Services (CMS) changed the payment method for Medicare (Part A) skilled nursing facility (SNF) care from a cost-based system to a prospective payment system (PPS). Unlike the previous cost-based payment system, PPS restricts skilled nursing facility payment to pre-determined levels. CMS also reduced the total payments to SNFs coincident with PPS implementation. These changes might reduce quality of care at skilled nursing facilities and could be reflected in resident discharge patterns. The present study examines the effect of the 1998 policy change on resident discharge outcomes. The results indicate that PPS reduced the relative risk of discharge to home and to death for Medicare residents (compared to non-Medicare residents) and had no significant effect on hospitalizations or transfers.